2021
DOI: 10.3390/ijms22168758
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Expansion Mechanism and Expression Profiling Analysis of GLABROUS1 Enhancer-Binding Protein (GeBP) Gene Family in Gramineae Crops

Abstract: The GLABROUS1 enhancer-binding protein (GeBP) gene family encodes a typical transcription factor containing a noncanonical Leucine (Leu-)-zipper motif that plays an essential role in regulating plant growth and development, as well as responding to various stresses. However, limited information on the GeBP gene family is available in the case of the Gramineae crops. Here, 125 GeBP genes from nine Gramineae crops species were phylogenetically classified into four clades using bioinformatics analysis. Evolutiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…The conserved motif analysis of the Arabidopsis GeBP sequence revealed that it possesses a basic amino acid region and a leucine zipper region, suggesting that GeBP may belong to the bZIP transcription factor family. However, it was found that the interval between these two conserved domains exceeds 9 residues, which is not a standard definition of a bZIP protein [ 7 , 8 ]. N-x7-R/K-x9-L-x6-L-x6-L is the basic structure of a typical bZIP conserved domain, which includes alkaline domains and Leu zipper domain separated by 9 residues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conserved motif analysis of the Arabidopsis GeBP sequence revealed that it possesses a basic amino acid region and a leucine zipper region, suggesting that GeBP may belong to the bZIP transcription factor family. However, it was found that the interval between these two conserved domains exceeds 9 residues, which is not a standard definition of a bZIP protein [ 7 , 8 ]. N-x7-R/K-x9-L-x6-L-x6-L is the basic structure of a typical bZIP conserved domain, which includes alkaline domains and Leu zipper domain separated by 9 residues.…”
Section: Introductionmentioning
confidence: 99%
“…Plants 2022, 11, 1848 2 of 13 However, it was found that the interval between these two conserved domains exceeds 9 residues, which is not a standard definition of a bZIP protein [7,8]. N-x7-R/K-x9-L-x6-L-x6-L is the basic structure of a typical bZIP conserved domain, which includes alkaline domains and Leu zipper domain separated by 9 residues.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that AtGeBP might participate in plant trichome formation. In addition, it was reported that GeBP family genes were involved in plant responses to phytohormones such as gibberellin [ 18 , 42 , 44 , 45 ], cytokinin [ 45 , 46 , 47 , 48 ], and auxin [ 45 ]. Furthermore, their roles in plant responses to environmental stresses such as heavy metals and pathogens were also reported [ 38 , 45 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was reported that GeBP family genes were involved in plant responses to phytohormones such as gibberellin [ 18 , 42 , 44 , 45 ], cytokinin [ 45 , 46 , 47 , 48 ], and auxin [ 45 ]. Furthermore, their roles in plant responses to environmental stresses such as heavy metals and pathogens were also reported [ 38 , 45 , 49 ]. For example, GeBP-like 4 ( GPL4 ) was induced in response to cadmium, copper, and zinc stresses in Arabidopsis [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation